Structural polymorphism in the promoter of pfmrp2 confers Plasmodium falciparum tolerance to quinoline drugs. Issue 5 (23rd January 2014) - Mok, Sachel; Liong, Kek‐Yee; Lim, Eng‐How; Huang, Ximei; Zhu, Lei; Preiser, Peter Rainer; Bozdech, Zbynek
Summary Drug resistance in Plasmodium falciparum remains a challenge for the malaria eradication programmes around the world. With the emergence of artemisinin resistance, the efficacy of the partner drugs in the artemisinin combination therapies (ACT) that include quinoline‐based drugs is becoming critical. So far only few resistance markers have been identified from which only two transmembrane transporters namely PfMDR1 (an ATP‐binding cassette transporter) and PfCRT (a drug‐metabolite transporter) have been experimentally verified. Another P. falciparum transporter, the ATP‐binding cassette containing multidrug resistance‐associated protein (PfMRP2) represents an additional possible factor of drug resistance in P. falciparum. In this study, we identified a parasite clone that is derived from the 3D7 P. falciparum strain and shows increased resistance to chloroquine, mefloquine and quinine through the trophozoite and schizont stages. We demonstrate that the resistance phenotype is caused by a 4.1 kb deletion in the 5′ upstream region of the pfmrp2 gene that leads to an alteration in the pfmrp2 transcription and thus increased level of PfMRP2 protein. These results also suggest the importance of putative promoter elements in regulation of gene expression during the P. falciparum intra‐erythrocytic developmental cycle and the potential of genetic polymorphisms within these regions to underlie drug resistance.